2022
DOI: 10.1039/d1cp05685a
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in Mo–P compounds under pressure and in double-Weyl semimetal Hex-MoP2

Abstract: Based on first-principles calculations, we predict five global stable molybdenum phosphorus compounds under the pressure range of 0-300 GPa. All of them display superconductivity with different transition temperatures. Meanwhile, we...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
1
1
0
Order By: Relevance
“…We find that the most stable configurations of the Mo-C systems are stacked by the component of H-Mo 2 C, which is energetically more stable than T-Mo 2 C. Although many MXenes have been synthesized in the T phase, [30][31][32][33][34] the H phase of 2D Mo x C y may be synthesized in the future. According to our calculations, similar to our recent study of the MoSH monolayer 61 and MoP 2 , 62 the Mo 4d orbitals are dominant at the Fermi level, while the C2p orbitals are negligible for most our studied 2D molybdenum carbides. Only in H-Mo 3 C 3 , when the C content is increased, the C 2p z orbital also contributes dominantly.…”
Section: Discussionsupporting
confidence: 88%
“…We find that the most stable configurations of the Mo-C systems are stacked by the component of H-Mo 2 C, which is energetically more stable than T-Mo 2 C. Although many MXenes have been synthesized in the T phase, [30][31][32][33][34] the H phase of 2D Mo x C y may be synthesized in the future. According to our calculations, similar to our recent study of the MoSH monolayer 61 and MoP 2 , 62 the Mo 4d orbitals are dominant at the Fermi level, while the C2p orbitals are negligible for most our studied 2D molybdenum carbides. Only in H-Mo 3 C 3 , when the C content is increased, the C 2p z orbital also contributes dominantly.…”
Section: Discussionsupporting
confidence: 88%
“…[20][21][22] It has been shown that the interaction between metal and hydrogen atoms under pressure induces favorable charge transfer from the hydrogen atom, which then further promotes a good superconducting performance. [23][24][25][26][27][28] Hence, the well-known barium hydride, BaH 6 (with a P4/mmm structure), can achieve a superconducting transition temperature (T c ) of 30-38 K at 100 GPa. 4,29 For lower barium hydride (BaH 2 ), which begins metallization at 44 GPa, its T c is unfortunately almost zero.…”
Section: Introductionmentioning
confidence: 99%